148k views
2 votes
−5(5x+3)−5x+1= -44
solve for X

2 Answers

6 votes

Answer:

x = 1

Explanation:

-5(5x+3) - 5x + 1 = -44

(-5*5x -5*3) - 5x + 1 = -44

(-25x - 15) - 5x + 1 = -44

-25x - 5x - 15 + 1 = -44

-30x - 14 = -44

-30x = -44 + 14

-30x = -30

x = -30/-30

x = 1

Check:

-5(/5*1) + 3) - 5*1 + 1 = -44

-5(5+3) - 5 + 1 = -44

-5*8 - 5 + 1 = -44

-40 - 5 + 1 = -44

-45 + 1 = -44

User Cloxure
by
6.9k points
3 votes

Answer:

x=1

Explanation:

Original Equation:


-5(5x+3)-5x+1= -44

Distribute the -5


-25x-15-5x+1= -44

Add like terms


-30x-14=-44

Add 14 to both sides


-30x=-30

Divide both sides by -30


x=1

User Allcaps
by
5.8k points